Al-Murtajal dan Al-Manqul dalam Serapan Bahasa Arab pada Nama-nama Masyarakat Indonesia dan Malaysia - Riadussolihin, Riadussolihin; Rahman, Roslan Bin Ab; Zulpadli, Lalu (Universitas Nusantara PGRI Kediri, 2024)
Arabic has made a major contribution to the development of the Malay language (Indonesia and Malaysia). The influence of Arabic can be seen from the large amount of vocabulary that has been absorbed and documented in books and dictionaries. Besides documented vocabulary, Arabic also influences the tradition of giving proper names among Indonesian and Malaysian people. However, data and analysis examining Arabic absorption names are still limited. This article aims to reveal and describe the phenomenon of absorption of al-'alam al-Murtajal and al-'alam al-Manqul, namely Arabic names and their vocabulary in the names of Indonesian and Malaysian people. This research is qualitative-descriptive, where the primary data sources are written documents and reviews of relevant literature. The results of this research show that the categories of Arabic names in the form of al-'alam al-Murtajal and al-'alam al-Manqul are absorbed and used in the names of Indonesian and Malaysian people. In the absorption process, there are two conditions, namely adoption and adaptation. The names included in al-'alam al-Murtajalwere adopted by the community without undergoing changes or shifts in terms of phonetics and spelling. Meanwhile, in al-'alam al-Manqul, adoption and adaptation processes coincide. Adopted names do not change, while adapted names change phonetics and spelling. As a result of this change, there is a semantic contradiction between the meaning of Arabic as a source language and the meaning desired by the absorbing community. Changes in letters and vowels can change the meaning from the perspective of the Arabic language, while these changes do not affect the desired meaning in the view of the people who absorb the name.